Transgenerational analysis about domestic violence through the genogram technique - Arias Gallegos, Walter L. (2017)
In the present study, we repot the results of the valuation of the family dynamics among people personas who were victims of domestic violence. For that, we adopted a family systemic approach and applied the genograms technique. We evaluated 79 people who went to the Public Ministry in Arequipa City, and were selected by quote sampling technique. As instruments there were used the sociodemographic chart, a predesign sheet for genograms drawing and a code chart. The data were processed by descriptive statistical methods, according to the nature of the information obtained. The results indicate that the 78.48% of people had suffered physical violence, being women in highest percentage (83.9%) and coming from nuclear families. Moreover, their relationships with their parents had been null or distanced, and about their own families, nuclear kind in the major proportion, the relationships were conflictive with their couples, and distant, fused, and conflictive with their children.